Our Destiny's Card: The Possibilities of the Subject-Object Financial Algorithm Interface - Nasrum, Muhammad (Journal of Legal and Cultural Analytics, 2025)
The study analyzed the practices of a community in Indonesia that uses credit cards and provided ethnographic cases where credit cards are used not only for consumption but also as productive capital for business. To provide important cultural background, the paper also examines pre-existing Indonesian financial systems, such as arisan—a form of rotating credit association deeply rooted in local culture. Temporalities, a common concept in anthropological studies of debt and credit, provide the analytic framework. It is also a strategy to dissect the credit card algorithm on a cultural level. This includes the features and roles of the credit cards, as perceived by community members, for decision making at each stage from application to business use. This cycle of social life demonstrates how such a financial instrument can be effective in delivering benefits and engendering trust within specific socio-cultural contexts.